Some freshwater algae from Bagh-Jhoda wetland, Morang: new for Nepal - Rajopadhyaya, Ritu; Rai, Shiva Kumar (Journal of Natural History Museum, 2018)
Present paper describes new and interesting algae reported during the exploration of algal flora of Bagh-Jhoda wetland, Morang. A total of 20 species of freshwater algae, excluding cyanobacteria, have been reported from this wetland as new for Nepal. They were Ankistrodesmus spiralis, Botryococcus braunii, B. protuberans, Glaucocystis duplex, Gonium sociale, Kirchneriella contorta, Nephrocytium hydrophilum, N.obesum, Oocystiseremosphaeria, Sorastrum americanum, Staurastrum pseudosebaldi, S. striolatum var. divergens, S. subpolymorphum, Glenodinium borgei, Peridinium gatunense, Gomphonema lacusrankaloides, G. pseudoaugur, Nitzschia cf. pumila, Pinnularia amabilis and Ulnaria capitata. This wetland area is rich in algal diversity including red algae and it needs further extensive exploration.